A practicum training in inland fisheries course conducted at freshwater aquaculture center CLSU, Nueva Ecija. - Gamboa, Lisette S. (College of Fisheries, University of the Philippines, 1979)
The practice in industry is a prerequisite for graduation in the Bachelor of Science in Fisheries. During the prescribed period, the student learns and obtains new experiences, expose them to the actual field practice and apply whatever theoretical knowledge they acquired. This would enable the students to help in the upliftment of fishery industry in the country. The training started on 27 March and ended on 23 April 1978 at the Freshwater Aquaculture Center in Central Luzon State University, Nueva Ecija. The work during the prescribed period was scheduled from 8-12 in the morning and 1-5 in the afternoon from Monday through Saturday. This report embraces the various activities participated in and the practice as well as the scientific knowledge learned by the author.